POSTCOLONIALISM AND SELECTED FICTIONAL WORKS OF PAUL SCOTT AND ROHINTON MISTRY - Khalid Altaf Sheikh, (International Journal of Innovations in Engineering Research and Technology, 2023)
This concept came as a reaction against the idea of colonial thought. It is a reaction against all the postcolonial tendencies of Britain and Europe. It studies the struggle of cultures or individuals against imperial political and individual power. Here an author can direct his attention on a tussle between power and the powerless, African and Asian countries and those backward educationally are represented in a lower light. This is a literary, cultural, social, and reformist movement, which speaks for the voiceless, backward, and downtrodden and aims at the displacement of those who are colonial rulers and have done nothing for the development of the common masses. Theories like Colonialism, Imperialism, Orientalism, Subaltern, Hybridity, Multiculturalism, Alienation, Uprootedness, Crisis of Identity, Gender, Racism, and Caste,etc are studied concerning this subject.